MorphMaskFormer: a transformer-based deep segmentation model for multi-class Demirjian stage estimation from panoramic radiographs - Kiransal, Melike; Ozcelik, Salih Talha Alperen; Aydan, Tuba; Uzen, Huseyin; Firat, Huseyin; Sengur, Abdulkadir; Duman, Suayip Burak (Elsevier Science Inc, 2026)
Objectives. This study aims to develop an advanced deep learning model that automatically determines third-molar developmental stages in panoramic radiographs using the Demirjian classification, improving the accuracy and objectivity of dental age estimation for forensic and clinical applications. Study Design. A total of 888 panoramic radiographs from individuals aged 7 to 30 were annotated by 2 experts based on Demirjian's A-H staging system. The proposed model, MorphMaskFormer, is built upon the classical UNet architecture, incorporating a lightweight transformer attention module inspired by Mask2Former. The model performs both binary (tooth/background) and multi-class (A-H stages) segmentation. Its performance was evaluated using IoU, Dice coefficient, Precision, Recall, and inference time, and compared against UNet, ResUNet, DeepLabV3+, PSPNet, and SegNet. Results. MorphMaskFormer outperformed all baseline models, achieving a Dice score of 0.9461, IoU of 0.8985, and the fastest inference time at 78.59 ms. In multi-class segmentation, it showed high accuracy for stages A, D, and H, with an overall component accuracy of 72.41%. Conclusions. MorphMaskFormer enables precise pixel-level segmentation of dental developmental stages, reducing inter-observer variability and shortening evaluation time. Its high accuracy and efficiency make it a scalable tool that enhances diagnostic confidence and supports critical clinical and forensic age-estimation decisions. (Oral Surg Oral Med Oral Pathol Oral Radiol 2026;141:851-865)
Keywords: Age Estimation